Is It Truly Improvisational Exercise Push Students' Speaking Ability - Muhammad Aswad (Universitas Sulawesi Barat, 2017)
Improvisational exercises is a technique which consist three steps, they are preparation, modelling, and playing, that is preparation the teacher presents exercises, the students practice (modelling), and then procedure (playing)and the it provides three main goals; (1) the students pronounciation improve, (2) proper use of grammatical structure is reinforced, (3) vocabulary practice in enhanced. With this background, this research was quasi-experimental, with non-equivalent control group design. The sample consisted of two classes of students enrolled in 2013/2014 academic year, which one group was taken to be an experimental and the other to be a control group. The data obtained through the test were analysed by using statistical analysis. In conducting the research, the researcher used improvisational exercise technique to evaluate the students' speaking performance which covered by three components of speaking, such as: fluency, accuracy, and comprehensibility. The research findings shows thatthe use of improvisational exercise technique (presentation, modelling, and playing) in teaching speaking can improve the speaking performance of the eight year students of SMP Negeri 2 Majene significantly after being given treatment. The mean score of experimental group in post-test and control group were significantly different. The mean score of post-test in experimental group (3.36) was higher than control group (3.00).Thus, it is recomended for all English teacher to improve the students ability in speaking.